Bagaimana Evaluasi yang Efektif dalam Pembelajaran Matematika: Tinjauan Persepsi Guru Matematika - Azahra Rahmadia; Rhomiy Handican (Griya Journal of Mathematics Education and Application, 2023)
Evaluation is the process of collecting and analyzing in determining the achievement of learning objectives. Evaluation is a priority that must be carried out by a teacher in carrying out learning. but there are still obstacles experienced by teachers in evaluating, one of which is in choosing the method to be applied. this study aims to look at teacher perceptions of evaluation in the effective learning process of mathematics. this research is a descriptive qualitative study where this research will analyze the opinions of 27 teachers who were sampled. in this study, using a questionnaire as a tool to collect data on teacher perceptions to examine data descriptive methods were used. Based on the results of the study, it is known that teachers' perceptions of evaluation in the effective learning process of mathematics are at a good level where 63% of teachers agree that evaluation can help teachers in knowing the success of learning objectives. In addition, 66.7% of teachers think that evaluation can help teachers in determining more effective learning methods, however, evaluation should not be carried out without any strategy or method that has not been prepared. Where 70.4% of teachers said that before carrying out the evaluation they need to use an evaluation method to measure students' ability to understand mathematics material. Therefore, the existence of an evaluation is very helpful, especially in supporting the ability of students to what extent they understand the learning that has been delivered.